The Effect of Time Intervals on Heat Transfer to the Implant-Bone Interface during Preparation of a Titanium Abutment: An in Vitro Study - Raoofi S; Behboud Z (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Thermal injury during dental implant placement and restoration is a clinical concern as it may cause bone damage and compromise osseointegration. The threshold level for heat-induced cortical bone necrosis is 47°C for 60 seconds. Objectives: To measure the amount of heat transferred to the implant-bone interface when a two-piece or one-piece abutment was prepared in vertical and horizontal direction using various time intervals. Materials and Methods: Three groups of samples (n = 24), one-piece and two-piece implant and natural teeth, were used in this study to compare the amount of heat transferred to the implant-bone interface. This study used cooling system in the 10, 20, 30, and 60 seconds time intervals. The Thermocouples (K type) were attached to each sample at the crestal, middle and apical points. To have a similar condition with the oral cavity, each implant was embedded separately in transparent acrylic resin in a 37°C water bath. To have a constant cutting pressure, the turbine was fixed on the stable stand and a 100 g counterweight hanged to it. Then, the bath was fixed in front of it and cutting started at vertical and horizontal directions for 10, 20, 30, 60 seconds. Results: The maximum decrease from 37°C was observed in two-piece implant at the apical point (3.95°C) after 60 seconds and the minimum decrease was seen in one-piece implant at the crestal point (0.6°C) after 60 seconds. Also the minimum increase was observed in the natural teeth at the apical point (0.15°C) at 10 seconds and the maximum temperature increase was seen in one-piece implant at the apical point (1.95°C) at 20 seconds. Conclusions: Within the limitation of this study, it was concluded that to reduce the thermal damage on the bone tissue, an intermittent cut up to 20 seconds is acceptable. Cutting one-piece implant caused more heat transfer than that of two-piece implant